An Analysis of Telugu Suicides by Gender - Gopala Sarma Poduri (Indian Journal of Private Psychiatry)
Background: Gender differences are getting progressively narrowed in all fields. Aim: Evaluate the Telugu suicides to find out if any gender differences are there in various parameters in Telugu states. Methods: Suicide data from the national portal were analyzed to find out gender differences in cause, education, income, method, profession, rate, and social status, for the period 1967–2021 before bifurcation (1967–2013) and after bifurcation (2014–2021). Further, differences between the two states were analyzed separately. Simple basic statistics and Wilcoxon signed-rank test were used to compare parameters. Results: There were a total of 471,285 Telugu suicides in the 56-year period of 1966–2021. Sex ratio (male/female) was 2.55. The lowest no. of suicides was recorded in 1980 (1,905) and the highest in 2021 (18,238). Female suicides recorded a reduction after bifurcation to an average of 29.1%. There was a marginal reduction in suicide after bifurcation due to reduced female suicides. The predominance of male suicides over women was maintained all through the recorded period. This continued even when the state was bifurcated. The contribution of Telugu suicides to total suicides was 9.8%. In most of the parameters studied, there were differences between the sexes. Telangana persistently recorded a higher rate. Conclusions: Further in-depth analysis is required to correlate with other associated parameters to identify sex-specific factors for suicide.